Conflict and harmony in comparative philosophy : selected works from the 2013 Joint Meeting of the Society for Asian and Comparative Philosophy and the Australasian Society for Asian and Comparative Philosophy /: selected works from the 2013 Joint Meeting of the Society for Asian and Comparative Philosophy and the Australasian Society for Asian and Comparative Philosophy. (2015) - Unknown
No abstract available